Parental perception of male circumcision: a local cross sectional study in a Muslim community - Abdullatif K. Al-Maghlouth; Ossama M. Zakaria (African Journal of Urology)
Abstract Background Male circumcision is regarded as one of the oldest and widely conducted surgical procedures. It entails partial or total removal of the prepuce skin. Recent human rights advocates have a higher dispute as regards circumcision. However, controversy still exists regarding the necessity of the procedure. The opponent considers it against human rights. On the other hand, supporters claim its hygiene and advantages in preventing urinary tract infections, sexually transmitted illnesses, and human immunodeficiency virus. Methods A specially designed anonymous cross-sectional questionnaire was distributed randomly among participants of a local Muslim community. Information such as sociodemographic characteristics, medical history, knowledge about male circumcision, and sources of information were collected. The collected data were statistically analyzed via the Statistical Packages for Software Sciences (SPSS) version 26.0. Results Four hundred and forty participated in the current study. The most commonly agreed upon indication for male circumcision by the participants was religion (88.4%). They considered it as a holy obligation. Circumcision-related hemorrhage was recognized as the most prevalent circumcision complication, followed by adhesions and infections. Overall, the majority of respondents were aware of the procedure itself, although a respectable percentage of participants (85%) supported the male circumcision. Conclusion The majority of the participants supported male circumcision as an obligatory religious deed. Moreover, they do believe in its medical benefits. Extra studies with larger cohort are needed for more reliable and realistic conclusions in the Islamic culture about male circumcision.